Differential Equations and Linear Algebra (4th Edition)

Published by Pearson
ISBN 10: 0-32196-467-5
ISBN 13: 978-0-32196-467-0

Chapter 4 - Vector Spaces - 4.4 Spanning Sets - Problems - Page 283: 37



Work Step by Step

We know that if $av_1+bv_2=v$, then $a+2b=3,-a+b=3,2a+3b=4$. Thus $(a+2b)+(-a+b)=3+3\\3b=6\\b=2$ $-a+b=-a+2=3\\a=-1$ And this satisfies the last equation because$2(-1)+3(2)=-2+6=4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.